Indonesia - Lestari, Rahayu; Murtopo, Bahrun Ali; Maryanto, Maryanto (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2022)
The aims of this study were to describe the use of singing method as an effort to increase interest in learning Arabic for the fifth-grade students of MI Ma’arif NU Tanjungsari and to find out the learning interest of the fifth-grade students of MI Ma’arif NU Tanjungsari in learning Arabic make use of the singing method. This research was conducted using a descriptive qualitative approach. The research subjects in this study were fifth grade student’s, Arabic Language teachers, principals and fifth student’s guardians of MI Ma’arif NUTanjungsari. The collection of data that is used by observations, interviews and documentation. The data analysis used is data reduction, data and conclusion drawing. To check the validity of data obtain using triangulation techniques. The results of study obtain that the use of the singing method in learning Arabic at the fifth grade by utilizing the song used to convey vocabulary material in chapter/theme 6 and carried oute like learning using other methods namely by the planning process, implementation and evaluation; the learning interest of fifth grade students in learning Arabic through the singing method has increased even though it has not been maximized. The fifth-grade students’ interest in learning Arabic through the singingmethod can be said to be good, although not optimal. This is indicated by the majority of students showing feelings of pleasure in learning, having the center of attention and thoughts on learning, having the center of attention and thoughts on learning, having a willingness to learn, having an inner willingness to be active in learning, making efforts to manifest a real desire to learn.